Effect of M1 protein and low pH on nuclear transport of influenza virus ribonucleoproteins. - Bui, M (1996)
Influenza virus enters its host cell by receptor-mediated endocytosis followed by acid-activated membrane fusion in endosomes. The viral ribonucleoprotein particles (vRNPs) delivered into the cytosol then dissociate from the matrix protein, M1, and from each other, after which they are individually imported into the nucleus via the nuclear pores. For some time, it has been believed that the low pH in endosomes may, in some way, trigger the capsid disassembly events necessary for nuclear transport. This report provides direct evidence that the association of M1 with vRNPs is sensitive to mildly acidic pH within the infected cell. Recombinant M1, expressed in cultured cells, was found to associate with vRNPs and inhibit their nuclear import. Brief acidification of the cytosolic compartment eliminated the interfering activity and allowed the incoming vRNPs to enter the nucleus. Newly assembled progeny M1-vRNP complexes in the cytosol of infected cells were also dissociated by brief acidification. Acidic pH was thus found to serve as a switch that allowed M1 to carry out its multiple functions in the uncoating, nuclear transport, and assembly of vRNPs.